2011
DOI: 10.1016/j.atherosclerosis.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial lipase (EL) and EL-generated lysophosphatidylcholines promote IL-8 expression in endothelial cells

Abstract: ObjectivePreviously we identified palmitoyl-lysophosphatidylcholine (LPC 16:0), as well as linoleoyl-, arachidonoyl- and oleoyl-LPC (LPC 18:2, 20:4 and 18:1) as the most prominent LPC species generated by the action of endothelial lipase (EL) on high-density lipoprotein (HDL). In the present study, the impact of EL and EL-generated LPC on interleukin-8 (IL-8) synthesis was examined in vitro in primary human aortic endothelial cells (HAEC) and in mice.Methods and ResultsAdenovirus-mediated overexpression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…VCAM1 is a cell adhesion molecule that mediates adhesion of leukocytes to vascular endothelium, leading to vascular inflammation, one of the early stages in atherosclerosis development. On the other hand, Riederer et al [61] showed the pro-inflammatory side of EL lipase activity. Interleukin 8 (IL-8) is a pro-inflammatory chemokine and is implicated in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM1 is a cell adhesion molecule that mediates adhesion of leukocytes to vascular endothelium, leading to vascular inflammation, one of the early stages in atherosclerosis development. On the other hand, Riederer et al [61] showed the pro-inflammatory side of EL lipase activity. Interleukin 8 (IL-8) is a pro-inflammatory chemokine and is implicated in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we provide evidence that the LXR agonist inhibits LPC‐induced IL‐8 overexpression in HUVECs, which has a biological effect on the firm adhesion of monocytes to the endothelial cells. Lysophosphatidylcholine is a major phospholipid component of ox‐LDL that induces IL‐8 expression and drives monocyte adhesion to endothelial cells via Ca 2+ signaling and NF‐κB pathway, which appear to be responsible for early stage atherogenesis . The LPC model in this study provided an opportunity to examine time‐ and dose‐dependent regulatory mechanisms, such as phosphorylation, ubiquitination and SUMOylation of NF‐κB.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that observed in the LPS-untreated effects of LysoPA and LysoPC on inflammatory cytokines and/or ER stress in other cells involved in atherosclerotic diseases. In particular, LysoPA promotes the release of the chemokine CXCL1 and the accumulation of macrophages in the endothelium of atherosclerotic lesions 3,24) , while LysoPC promotes the expression of IL-8, a proinflammatory and proadhesive chemokine 25) . Regarding ER stress, LysoPA reportedly attenuates ER stress and ER stress-associated apoptosis in murine mesenchymal stem cells 26) .…”
Section: The Lysops Receptor Expression Differed Among the Lps-untreamentioning
confidence: 99%